Adsorpsi Zat Warna Rhodamine-B Menggunakan Fly Ash Sawit Yang Dimodifikasi Dengan NaOH Sebagai Adsorben - Charismayani Charismayani; Edy Saputra; Ahmad Fadli (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Rhodamine B contributes significantly to environmental pollution, because it is nonbiodegradable, toxic and harmful to the environment. One effort to reduce the amount of Rhodamine B is the adsorption process. The purpose of this study to determine the effect of adsorption temperature, pH, adsorbent mass. Knowing the optimum conditions for reducing the levels of dye in the water, as well as determine the adsorption equilibrium modelsRhodamine B using fly ash oil modified with 1.4 NaOH as an adsorbent. fly ash modification processes are done by mixing fly ash and NaOH in the ratio 1: 4. The adsorption process isconducted by mixing fly ash oil and pH solution of rhodamine B. The optimum conditions for reducing the levels of rhodamine B in water is the adsorbent mass of 5 g/L, temperature of45°C and pH 2. Thermodynamic data such as ΔH, ΔG and ΔS were calculated. And the mechanism of rhodamine B dye adsorption by fly ash oil is dominated by Freundlich isotherm models representing physical adsorption.Keyword: Adsorption, Rhodamine B, Fly Ash, Isothermal Adsorption